Sonographic Findings in Septo-Optic Dysplasia in the Fetus and Newborn Infant - Pilu, Gianluigi; Sandri, Fabrizio; Cerisoli, Marziano; Alvisi, Carlo; Salvioli, Gian Paolo; Bovicelli, Luciano (American Journal of Perinatology, 1990)
A 28-year-old primigravida woman was referred for ultrasound studies at 27 weeks' gestation. Sonographic examination found enlarged cerebral ventricles, communicating lateral ventricles, bilateral cleft lip and palate. A 2500 gm male infant was delivered at 36 weeks' gestation, after which the diagnosis of septo-optic dysplasia was made.